2001
DOI: 10.1007/s007750000183
|View full text |Cite
|
Sign up to set email alerts
|

The design of new molecular "light switches" for DNA

Abstract: Two novel ruthenium(II) complexes, [Ru(pztp)2(phen)](ClO4)2 and [Ru(pztp)2(bpy)] (ClO4)2, have been synthesized and characterized by UV/Vis and 1H NMR spectroscopies and mass spectrometry. The MeCN solutions of both complexes display fluorescence that was found to be highly sensitive to the presence and concentration of water. The complexes behave like a "light switch" for DNA in that they do not luminesce in water but were "turned on" in the presence of DNA and show emission enhancement with the increase of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 135 publications
(56 citation statements)
references
References 0 publications
2
54
0
Order By: Relevance
“…We have been carrying out a systematic study of the interactions of Ru II -polypyridine complexes with DNA, and one of our aims is to find a sensitive luminescence probe for DNA. In our previous study, the complex [Ru(bpy) 2 ,10]phenanthroline) was developed to act as a molecular light switch for DNA in aqueous solution [24]; three other complexes, [Ru(phen) 2 ,10] phenanthroline) are also found to possess similar properties [32]. These results indicated that a complex whose luminescence intensity correlates well with the polarity of the medium might serve to explore the DNA -complex interaction.…”
Section: (Dppz)]mentioning
confidence: 90%
“…We have been carrying out a systematic study of the interactions of Ru II -polypyridine complexes with DNA, and one of our aims is to find a sensitive luminescence probe for DNA. In our previous study, the complex [Ru(bpy) 2 ,10]phenanthroline) was developed to act as a molecular light switch for DNA in aqueous solution [24]; three other complexes, [Ru(phen) 2 ,10] phenanthroline) are also found to possess similar properties [32]. These results indicated that a complex whose luminescence intensity correlates well with the polarity of the medium might serve to explore the DNA -complex interaction.…”
Section: (Dppz)]mentioning
confidence: 90%
“…These studies are closely related to the replication of DNA in vivo, mutation of genes, and action mechanisms of some DNA-targeted drugs [4][5][6]. Factors that determine the affinity and selectivity in binding of small molecules to DNA would be valuable in the design of new diagnostic and therapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Many metal complexes have the potential to be developed into novel probes of DNA structure [1][2][3][4][5], and can be used as mediators of duplex DNA cleavage reactions [6][7][8], as anticancer drugs [9] that control the reproduction of DNA in the body of living organs, as electron acceptors and donors for studying long-range electron transfer through DNA films [10][11][12], as hybridization indicators for DNA electrochemical biosensors [13][14][15][16][17][18][19][20][21], and as agents for DNA emission labels [22], just to name a few. In the last decades increasing efforts have been devoted to studying the interactions of metal complexes with double-stranded DNAs.…”
Section: Introductionmentioning
confidence: 99%